Acute effects of strength training on running economy - Ho, K.; Williams, M.; Wilson, C.; Lorenzen, C.; Meehan, D.; Joseph, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Sequencing strength training before aerobic conditioning is practised without empirical support. This study explored the acute effects of strength training on running economy and 3-D kinematics in five males. Running was performed on a treadmill at 12 and 14 km/h on three separate occasions. Trial 1 and 2 involved no strength training with data used to assess response stability of the variables. Before Trial 3, three sets of three repetitions at 85% of 1 repetition maximum of squat, bench press and deadlift with 3-5 minutes of rest were performed. Compared to Trial 2 no significant differences were observed when strength training was performed. Only a tendency of increased knee flexion (4.5°) at foot strike at the higher running velocity was observed. This suggests that running kinematics were changed exposing participants to long-term chronic injuries.